Development, women, and war : feminist perspectives - Afshar, Haleh; Eade, Deborah (Oxfam, 2004)
The shared experiences of women and their potential to contribute both to war and particularly to peace are highlighted in this discussion of the long-running conflicts in the Middle East, Africa and Eastern Europe. Policy makers, practitioners and academics consider why womens concerns have yet to be placed at the forefront of both analysis and practical outcomes. This selection of essays presents an overview of different feminist approaches to peace building and conflict resolution and puts forward concrete policy measures to achieve these ends. Contributors argue for the need to move beyond the myriad projects that involve women to consider the factors that contribute to the relatively poor overall impact of such projects - an outcome that often results from a failure to understand the underlying gendered power relations and the dynamics of social change